Performance Analysis of a Parabolic Trough Collector with Photovoltaic—Thermal Generation: Case Study and Parametric Study - Benjamín Chavarría-Domínguez; Susana Estefany De León-Aldaco; Mario Ponce-Silva; Nicolás Velázquez-Limón; Jesús Armando Aguilar-Jiménez; Fernando Chavarría-Domínguez; Ernesto Raúl Rodríguez-García; Heriberto Adamas-Pérez; Ricardo Eliu Lozoya-Ponce; Eligio Flores-Rodriguez (Energies)
This study presents a mathematical model of a parabolic trough solar collector with photovoltaic cells integrated into its solar receiver. A case study is presented, utilizing meteorological data obtained from the localities of Cuernavaca and Mexicali in Mexico. The results demonstrate moderately variable electrical and thermal energy production for Cuernavaca (387.93 kWh to 239.38 kWh and 1036.11 kWh to 641.26 kWh, respectively). In contrast, the production of electrical and thermal energy in Mexicali exhibited considerably greater fluctuations (515.16 kWh to 177.69 kWh and 1424.39 kWh to 448.88 kWh, respectively). Furthermore, a parametric study is presented, which analyzes the impact of solar receiver geometry and mass flow on the model’s behavior. The results demonstrate that the pipe length exerts the most significant influence on the electrical and thermal power output (1.21 kW to 2.22 kW and 3.7 kW to 6.9 kW, respectively). Additionally, the diameter has an impact on the thermal power output (5.23 kW to 7.1 kW) and the electrical and thermal efficiency (0.18 to 0.15 and 0.54 to 0.74, respectively). Modifying the mass flow facilitates the enhancement of electrical power and efficiency (1.54 kW to 1.72 kW and 0.16 to 0.18, respectively) while concurrently preventing a significant reduction in thermal power and efficiency (5.4 kW to 5.3 kW and 0.56 to 0.55, respectively). A script with the developed model is provided.